Clinical evaluations of diaphysis malignant tumors of femur and tibia treated with microwave ablation in situ - Yu, Zhe (J Orthop Surg Res, 2020)
BACKGROUND: This study was designed to evaluate the clinical outcomes of patients with diaphysis malignant tumors of femur and tibia treated with microwave ablation (MWA) in situ. METHODS: Retrospective study of 32 patients with diaphysis malignant bone tumors of femur or tibia have been treated by microwave ablation. Instead of en bloc resection, hyperthermia ablation in situ was carried out followed by strengthen procedure. The patients were followed up for a period ranging from 36 to 180 months. RESULTS: Twenty-five patients survived over 3 years and all of the patients alive have a satisfactory functional and cosmetic limb. The postoperative survival rate of MWA group was significantly higher than the amputation group in consecutive inclusions. CONCLUSIONS: MWA is a feasible and effective surgical method for limb salvage operation and it might offer an innovative and distinctive therapeutic alternative for diaphysis malignant bone tumors, which avoiding osteotomy or prosthesis replacement. LEVEL OF EVIDENCE: Level IV, clinical cohort study